Evaluating the physicochemical properties and efficacy of recently expired and aged antivenom products from Thailand and Taiwan - Tan, Kae Yi; Liew, Sin Teng; Tan, Qian Yi; Abdul-Rahman, Farah Nadhirah; Azmi, Nor Izzati; Sim, Si Mui; Tan, Nget Hong; Khomvilai, Sumana; Sitprija, Visith; Tan, Choo Hock (Elsevier, 2019)
Gel filtration chromatography and gel electrophoresis revealed minimal protein degradation in lyophilized antivenoms which were 2-year expired (Hemato Polyvalent, Neuro Polyvalent; Thailand) and 18-year expired (Hemato Bivalent, Neuro Bivalent; Taiwan). All expired antivenoms retained immunological binding activity, and were able to neutralize the hemotoxic or neurotoxic as well as lethal effects of the homologous snake venoms. The findings show that antivenoms under proper storage conditions may remain relatively stable beyond the indicated shelf life. © 2019 Elsevier Ltd